Pengaruh Pelatihan dan Motivasi Terhadap Produktivitas Kerja Pegawai (Study pada Idea Batik Gondanglegi Kabupaten Malang) - Ahmad Mahsunun Nashor; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Every organization in a company operates by using all of its resources to be able to produce products, both goods/services that can be marketing. This study aims to determine the effect of training and motivation on employee work productivity at Idea Batik Gondanglegi Malang Regency simultaneously and partially. This type of research is associative quantitative research. The research was conducted at Idea Batik Gondanglegi, Malang Regency. The time for this research to be carried out is from September to December 2021. The population and sample used are Idea Batik Gondanglegi employees, totaling 38 people. Based on the research results, it is known that training and motivation simultaneously affect the work productivity of employees in Idea Batik Gondanglegi, Malang Regency. partially or individually training and motivation affect the work productivity of employees in Idea Batik Gondanglegi Malang Regency. Keywords: Training, Motivation, Employee work productivity